False or Fake Qualifications in an Employment Context: A South African Perspective - Ndlovu, Lonias; Leslie, Andrew Brian (Yuridika, 2022)
The pressure for employment opportunities has led to many dishonest practices by employees and job seekers. The evil of employees misrepresenting their academic qualifications has become endemic, and the South African government has been compelled to act. Misrepresentation of academic qualifications mainly manifests itself through employees claiming to have non-existent higher education qualifications to secure a new job offer or be promoted to a higher post. This misrepresentation has consequences for the employer, who may pay the employee a salary they do not deserve. The employee must refund the employer and face prospects of imprisonment if found guilty in a criminal court. In South Africa, high-profile individuals working in the public service or occupying prominent political positions have falsely claimed to have qualifications that they did not have. They have been allowed to resign on their own accord or were dismissed after lengthy disciplinary hearings. This paper outlines some examples of this misrepresentation and unravels the legal implications from a South African perspective. We recommend that employers promptly discipline employees found guilty rather than allow them to resign, as was done correctly in the Mthikhulu case discussed here. Further, we urge employers in South Africa to foreground the skills of employees rather than paper qualifications and assess technical ability ahead of academic qualifications.